6.186 Problems 18501 to 18600

Table 6.371: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

18501

\[ {}1+2 x+\left (-t^{2}+4\right ) x^{\prime } = 0 \]

18502

\[ {}x^{\prime } = \cos \left (\frac {x}{t}\right ) \]

18503

\[ {}\left (t^{2}-x^{2}\right ) x^{\prime } = t x \]

18504

\[ {}{\mathrm e}^{3 t} x^{\prime }+3 x \,{\mathrm e}^{3 t} = 2 t \]

18505

\[ {}2 t +3 x+\left (3 t -x\right ) x^{\prime } = t^{2} \]

18506

\[ {}x^{\prime }+2 x = {\mathrm e}^{t} \]

18507

\[ {}x^{\prime }+x \tan \left (t \right ) = 0 \]

18508

\[ {}x^{\prime }-x \tan \left (t \right ) = 4 \sin \left (t \right ) \]

18509

\[ {}t^{3} x^{\prime }+\left (-3 t^{2}+2\right ) x = t^{3} \]

18510

\[ {}x^{\prime }+2 t x+t x^{4} = 0 \]

18511

\[ {}t x^{\prime }+x \ln \left (t \right ) = t^{2} \]

18512

\[ {}t x^{\prime }+x g \left (t \right ) = h \left (t \right ) \]

18513

\[ {}t^{2} x^{\prime \prime }-6 t x^{\prime }+12 x = 0 \]

18514

\[ {}x^{\prime } = -\lambda x \]

18515

\[ {}[x^{\prime }\left (t \right ) = x \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )+2 y \left (t \right )] \]

18516

\[ {}t^{2} x^{\prime \prime }-2 t x^{\prime }+2 x = 0 \]

18517

\[ {}x^{\prime \prime }-5 x^{\prime }+6 x = 0 \]

18518

\[ {}x^{\prime \prime }-4 x^{\prime }+4 x = 0 \]

18519

\[ {}x^{\prime \prime }-4 x^{\prime }+5 x = 0 \]

18520

\[ {}x^{\prime \prime }+3 x^{\prime } = 0 \]

18521

\[ {}x^{\prime \prime }-3 x^{\prime }+2 x = 0 \]

18522

\[ {}x^{\prime \prime }+x = 0 \]

18523

\[ {}x^{\prime \prime }+2 x^{\prime }+x = 0 \]

18524

\[ {}x^{\prime \prime }-2 x^{\prime }+2 x = 0 \]

18525

\[ {}x^{\prime \prime }-x = t^{2} \]

18526

\[ {}x^{\prime \prime }-x = {\mathrm e}^{t} \]

18527

\[ {}x^{\prime \prime }+2 x^{\prime }+4 x = {\mathrm e}^{t} \cos \left (2 t \right ) \]

18528

\[ {}x^{\prime \prime }-x^{\prime }+x = \sin \left (2 t \right ) \]

18529

\[ {}x^{\prime \prime }+4 x^{\prime }+3 x = t \sin \left (t \right ) \]

18530

\[ {}x^{\prime \prime }+x = \cos \left (t \right ) \]

18531

\[ {}x^{2} y^{\prime \prime }-\frac {x^{2} {y^{\prime }}^{2}}{2 y}+4 x y^{\prime }+4 y = 0 \]

18532

\[ {}y^{\prime }+c y = a \]

18533

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{x}+k^{2} y = 0 \]

18534

\[ {}\cos \left (x \right ) y^{\prime }+\sin \left (x \right ) y^{\prime \prime }+n y \sin \left (x \right ) = 0 \]

18535

\[ {}y^{\prime } = \frac {\sqrt {1-y^{2}}\, \arcsin \left (y\right )}{x} \]

18536

\[ {}v^{\prime \prime } = \left (\frac {1}{v}+{v^{\prime }}^{4}\right )^{{1}/{3}} \]

18537

\[ {}v^{\prime }+u^{2} v = \sin \left (u \right ) \]

18538

\[ {}\sqrt {y^{\prime }+y} = \left (y^{\prime \prime }+2 x \right )^{{1}/{4}} \]

18539

\[ {}v^{\prime }+\frac {2 v}{u} = 3 \]

18540

\[ {}\sin \left (x \right ) \cos \left (y\right )^{2}+\cos \left (x \right )^{2} y^{\prime } = 0 \]

18541

\[ {}y^{\prime }+\sqrt {\frac {1-y^{2}}{-x^{2}+1}} = 0 \]

18542

\[ {}-x y^{\prime }+y = b \left (1+x^{2} y^{\prime }\right ) \]

18543

\[ {}x^{\prime } = k \left (A -n x\right ) \left (M -m x\right ) \]

18544

\[ {}y^{\prime } = 1+\frac {1}{x}-\frac {1}{y^{2}+2}-\frac {1}{x \left (y^{2}+2\right )} \]

18545

\[ {}y^{2} = x \left (y-x \right ) y^{\prime } \]

18546

\[ {}2 x^{2} y+y^{3}-x^{3} y^{\prime } = 0 \]

18547

\[ {}2 a x +b y+\left (2 c y+b x +e \right ) y^{\prime } = g \]

18548

\[ {}\sec \left (x \right )^{2} \tan \left (y\right ) y^{\prime }+\sec \left (y\right )^{2} \tan \left (x \right ) = 0 \]

18549

\[ {}x +y y^{\prime } = m y \]

18550

\[ {}\frac {2 x}{y^{3}}+\left (\frac {1}{y^{2}}-\frac {3 x^{2}}{y^{4}}\right ) y^{\prime } = 0 \]

18551

\[ {}\left (T+\frac {1}{\sqrt {t^{2}-T^{2}}}\right ) T^{\prime } = \frac {T}{t \sqrt {t^{2}-T^{2}}}-t \]

18552

\[ {}y^{\prime }+x y = x \]

18553

\[ {}y^{\prime }+\frac {y}{x} = \sin \left (x \right ) \]

18554

\[ {}y^{\prime }+\frac {y}{x} = \frac {\sin \left (x \right )}{y^{3}} \]

18555

\[ {}p^{\prime } = \frac {p+a \,t^{3}-2 p t^{2}}{t \left (-t^{2}+1\right )} \]

18556

\[ {}\left (T \ln \left (t \right )-1\right ) T = t T^{\prime } \]

18557

\[ {}y^{\prime }+y \cos \left (x \right ) = \frac {\sin \left (2 x \right )}{2} \]

18558

\[ {}y-\cos \left (x \right ) y^{\prime } = y^{2} \cos \left (x \right ) \left (1-\sin \left (x \right )\right ) \]

18559

\[ {}x {y^{\prime }}^{2}-y+2 y^{\prime } = 0 \]

18560

\[ {}2 {y^{\prime }}^{3}+{y^{\prime }}^{2}-y = 0 \]

18561

\[ {}y^{\prime } = {\mathrm e}^{z -y^{\prime }} \]

18562

\[ {}\sqrt {t^{2}+T} = T^{\prime } \]

18563

\[ {}\left (x^{2}-1\right ) {y^{\prime }}^{2} = 1 \]

18564

\[ {}y^{\prime } = \left (x +y\right )^{2} \]

18565

\[ {}\theta ^{\prime \prime } = -p^{2} \theta \]

18566

\[ {}\sec \left (\theta \right )^{2} = \frac {m s^{\prime }}{k} \]

18567

\[ {}y^{\prime \prime } = \frac {m \sqrt {1+{y^{\prime }}^{2}}}{k} \]

18568

\[ {}\phi ^{\prime \prime } = \frac {4 \pi n c}{\sqrt {v_{0}^{2}+\frac {2 e \left (\phi -V_{0} \right )}{m}}} \]

18569

\[ {}y^{\prime } = x \left (y^{2} a +b \right ) \]

18570

\[ {}n^{\prime } = \left (n^{2}+1\right ) x \]

18571

\[ {}v^{\prime }+\frac {2 v}{u} = 3 v \]

18572

\[ {}\sqrt {-u^{2}+1}\, v^{\prime } = 2 u \sqrt {1-v^{2}} \]

18573

\[ {}\sqrt {1+v^{\prime }} = \frac {{\mathrm e}^{u}}{2} \]

18574

\[ {}\frac {y^{\prime }}{x} = y \sin \left (x^{2}-1\right )-\frac {2 y}{\sqrt {x}} \]

18575

\[ {}y^{\prime } = 1+\frac {2 y}{x -y} \]

18576

\[ {}v^{\prime }+2 v u = 2 u \]

18577

\[ {}1+v^{2}+\left (u^{2}+1\right ) v v^{\prime } = 0 \]

18578

\[ {}u \ln \left (u \right ) v^{\prime }+\sin \left (v\right )^{2} = 1 \]

18579

\[ {}4 y {y^{\prime }}^{3}-2 x^{2} {y^{\prime }}^{2}+4 x y y^{\prime }+x^{3} = 16 y^{2} \]

18580

\[ {}\theta ^{\prime \prime }-p^{2} \theta = 0 \]

18581

\[ {}y^{\prime \prime }+y = 0 \]

18582

\[ {}y^{\prime \prime }+12 y = 7 y^{\prime } \]

18583

\[ {}r^{\prime \prime }-a^{2} r = 0 \]

18584

\[ {}y^{\prime \prime \prime \prime }-a^{4} y = 0 \]

18585

\[ {}v^{\prime \prime }-6 v^{\prime }+13 v = {\mathrm e}^{-2 u} \]

18586

\[ {}y^{\prime \prime }+4 y^{\prime }-y = \sin \left (t \right ) \]

18587

\[ {}y^{\prime \prime }+3 y = \sin \left (x \right )+\frac {\sin \left (3 x \right )}{3} \]

18588

\[ {}5 x^{\prime }+x = \sin \left (3 t \right ) \]

18589

\[ {}x^{\prime \prime \prime \prime }-6 x^{\prime \prime \prime }+11 x^{\prime \prime }-6 x^{\prime } = {\mathrm e}^{-3 t} \]

18590

\[ {}x^{4} y^{\prime \prime \prime \prime }+x^{3} y^{\prime \prime \prime }-20 x^{2} y^{\prime \prime }+20 x y^{\prime } = 17 x^{6} \]

18591

\[ {}t^{4} x^{\prime \prime \prime \prime }-2 t^{3} x^{\prime \prime \prime }-20 t^{2} x^{\prime \prime }+12 t x^{\prime }+16 x = \cos \left (3 \ln \left (t \right )\right ) \]

18592

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }-y^{\prime }+y = 0 \]

18593

\[ {}y^{\prime \prime \prime \prime }-3 y^{\prime \prime \prime }+3 y^{\prime \prime }-y^{\prime } = {\mathrm e}^{2 x} \]

18594

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = \cos \left (x \right ) \]

18595

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+y = \frac {1}{x} \]

18596

\[ {}y^{\prime \prime } = c \left (1+{y^{\prime }}^{2}\right ) \]

18597

\[ {}y^{\prime \prime } = c \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}} \]

18598

\[ {}x^{3} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }+x y^{\prime }+y = 0 \]

18599

\[ {}y^{\prime \prime } = -m^{2} y \]

18600

\[ {}1+{y^{\prime }}^{2}+\frac {m y^{\prime \prime }}{\sqrt {1+{y^{\prime }}^{2}}} = 0 \]